Strategi Pelestarian Rumah Tradisional Pada Wilayah Pedesaan di Aceh (Studi Kasus: Rumoh Aceh di Gampong Lubuk Sukon, Aceh Besar) - Masdar Djamaludin; Hilda Mufiaty; Zulfikar Taqiuddin; Putri Baysita (Jurnal Serambi Engineering, 2024)
The number of traditional houses in Aceh called "Rumoh Aceh" is decreasing due to the changing needs and lifestyle of the Acehnese people, who prefer to build and live-in modern houses. Several Rumoh Aceh can still be found in rural areas in varying conditions but their numbers are decreasing. The well maintained Rumoh Aceh which are still inhabit by the owners are Rumoh Aceh in Lubok Sukon village, Aceh Besar. This phenomenon is the background for conducting this research, which aims to reveal the strategies carried out by community to preserve Rumoh Aceh. Qualitative research with in-depth interviews and observations was carried out to gather information from the owners and residents. Using purposive sampling method, 7 Rumoh Aceh which were 80 years old and over 100 years old, were selected for the case study. The results reveal that adaptation and revitalization strategies are the main strategies to preserve Rumoh Aceh. Adaptation is carried out by adding facilities and modifying the interior and exterior to accommodate modern needs and comfort. Revitalization is held by carrying out festives, cultural and religious activities. Rumoh is used as a museum and home stay and various tourist attraction events are also held to provide experience moments for visitors. The activities are known as experience tourism strategies.